Cut to the chase: does service quality or customer satisfaction effectively improve customer loyalty in the internet provider industry? - Djunaidy, Nurul Faizah Chairunnisa; Darmawan, Baziedy Aditya (Jurnal Mantik, 2024)
This study examines the influence of service quality and customer satisfaction on customer loyalty at PT. Telkom Indonesia's Ternate branch. Utilizing a quantitative approach, data were collected through a closed questionnaire from 70 customers who had directly interacted with Telkom’s services. The data were analyzed using descriptive methods and SmartPLS to explore the relationships between service quality, customer satisfaction, and customer loyalty. The results indicate that tangible and reliable aspects of service quality significantly enhance customer loyalty, while responsiveness does not have a notable effect. Additionally, customer satisfaction does not significantly influence loyalty and does not mediate the relationship between service quality and loyalty. These findings suggest that Telkom Ternate should prioritize improving tangible and reliable service dimensions to boost customer loyalty. This research offers practical insights for service improvement strategies to strengthen customer retention